The Poetic Genius of early Romanticism. Creative manifestation as a drive towards infinity - Cristiá, Felix Alejandro (2025)
This essay aims to analyze the concept of Romantic Poetic Genius as the maximum creative manifestation that does not aspire to synthesis, but to place itself beyond the need to achieve any synthesis, tending towards a different concept of infinity with respect to absolute idealism.